The Red Chili (Capsicum annum ) Anayisis of Production Eficient and income of Usahatani in Penengahan District South Lampung Regency - Eka Kasymir (Politeknik Negeri Lampung, 2011)
The Red Chili is one of horticulture product which has good economic value. Researcher tries to found which factor has influence of red chili production at Penengahan subdistrict South Lampung regency and also to know the profit of farming at Kecamatan Penengahan. This Research conducted Penengahan subdistrict, South Lampung regency. Sample was conducted by Simple Random Sampling. Respondents in this research are amount to 55 farmers of Kelaten and Gandri villages. The result of this research tells us that factors which influence of red chili production at Penengahan subdistrict are : field area, pesticide and farm labor. Seed, Urea fertilizer, NPK fertilizer are complement with field area. Red Chili farming at Penengahan subdistrict South Lampung regency was profitable which total profit Rp. 35.311.703,31 per hectare or (R/C) 2,00. It’s mean that every cost Rp. 1,00 will get income Rp. 2,00.Keywords: Capsicum annum, Production Efficient, Income